DIAGNOSIS JENIS PENYAKIT TANAMAN JATI (Tectona Grandis) PADA AREAL HUTAN TANAMAN DESA HATUSUA KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Jogeneis Patty; Costanza Uruilal (JURNAL HUTAN PULAU-PULAU KECIL, 2016)
Teak plantation forest development in the village Hatusua Kairatu District of West Seram regency is one attempt to offset the need for wood raw material increases. However, based on preliminary observations visible symptom of diseases such as leaf spot disease. Thus the need to do a diagnosis of the types of diseases in the forest area.The study aims to determine the types of diseases that attack plants teak (Tectona grandis) in the plantation areas Hatusua Rural District of West Seram regency Kairatu, determine the intensity of the disease as well as the extent of the damage and determine the condition of the teak plantations and support the development of the disease.The results showed that the types of diseases that are found is a leaf spot disease caused by the fungus Phomopsis sp. and root rot and stem are a symptom of a physiological disease. The disease intensity of leaf spot was 1,21 % and the disease intensity of root and stem rot 10,08 %, both of which belong to the category of minor assault. Conditions in the village area of teak plants Hatusua support the development of the disease.